A Case of ‘Multi-Inflammatory Syndrome in Children’ Complicated with Cardiogenic Shock - Biçer, Nazmiye Serap; Türe, Zeynep; Ülger, Birkan; Esmaoğlu, Aliye (European Journal of Therapeutics, 2022)
SARS Cov-2 infection causes Multi-Inflammatory Syndrome in Children (MIS-C), a serious condition that affects children. We report an 18-year-old Turkish male who was diagnosed with MIS-C and successfully treated. He was diagnosed with MIS-C and required invasive mechanical ventilation due to cardiogenic shock, after what he recovered. With a high temperature, rash, and conjunctival hyperemia, the patient was taken to the emergency department. He had no symptomatic COVID-19 in his medical history, although he had had contact with a COVID-19 positive patient in the near past. Physical examination revealed an erythematous maculopapular rash on the back and neck, as well as hepatosplenomegaly. SARS-CoV-2 IgM and IgG positivity were detected in the rapid antibody test. Following the procedure, rectal bleeding and tachypnea developed. Inflammation indicators and pro-BNP levels both increased. With echocardiogenic examination, the ejection fraction decreased from 50-55 percent to 35%. He needed invasive mechanical ventilation. As a result, the case was classified as MIS-C with predominant cardiac and gastrointestinal involvement. The patient was discharged after a successful multidisciplinary approach. Although COVID-19 infection in children and adolescents is asymptomatic or minimally symptomatic, clinicians should be aware of post-infection autoimmune complications.